PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM DAN IMPLEMENTASINYA DI MTS NURUL UMMAH YOGYAKARTA - Aset Sugiana (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2019)
This study aims to: describe the implementation of the PAI curriculum in the subjects of Aqeedah Akhlaq. This is a qualitative research. The research data were obtained from Aqeedah Akhlaq teacher in implementing PAI curriculum. Data analysis technique used is classifying, combining, interpreting, and concluding. The results of research on the development of the PAI curriculum: 1) Focusing on the development potential, needs, and interests of students and their environment, 2) Diverse and integrated, 3) Responsiveness to the development of science, technology, and art, 4) Relevant to the needs of life, 5) Comprehensive and continuous, 6) Lifelong learning, 7) Balance between national interests and regional interests. Implementation at MTs Nurul Ummah Yogyakarta, namely: 1) Organizing Workshops or socialization about making lesson plans, 2) Using textbooks from the Ministry of Religion and also pesantren (The Yellow Book), 3) Learning Aqeedah Akhlaq focuses on three aspects: cognitive, affective, and psychomotor, 4) Using the nahwu amtsilati learning method from Jepara and curriculum integration from Purworejo.